Experimental Study of Tumor Therapy Mediated by Multimodal Imaging Based on a Biological Targeting Synergistic Agent - Wang Y (Dove Medical Press, 2020)
Yaotai Wang,1 Chun Chen,1 Yong Luo,1 Jie Xiong,1 Yu Tang,1 Haiyan Yang,1 Lu Wang,1 Fujie Jiang,1 Xuan Gao,2 Die Xu,2 Huanan Li,1 Qi Wang,1 Jianzhong Zou1,2 1State Key Laboratory of Ultrasound in Medicine and Engineering, College of Biomedical Engineering, Chongqing Medical University, Chongqing 400016, People’s Republic of China; 2Chongqing Key Laboratory of Biomedical Engineering, Chongqing Medical University, Chongqing, 400016, People’s Republic of ChinaCorrespondence: Jianzhong ZouState Key Laboratory of Ultrasound in Medicine and Engineering, College of Biomedical Engineering, Chongqing Medical University, Yuzhong District, Chongqing 400016, People’s Republic of ChinaTel +86-13708302390Email zoujzh@cqmu.edu.cnPurpose: The high-intensity focused ultrasound (HIFU) ablation of tumors is inseparable from synergistic agents and image monitoring, but the existing synergistic agents have the defects of poor targeting and a single imaging mode, which limits the therapeutic effects of HIFU. The construction of a multifunctional biological targeting synergistic agent with high biosafety, multimodal imaging and targeting therapeutic performance has great significance for combating cancer.Methods: Multifunctional biological targeting synergistic agent consisting of Bifidobacterium longum (B. longum), ICG and PFH coloaded cationic lipid nanoparticles (CL-ICG-PFH-NPs) were constructed for targeting multimode imaging, synergistic effects with HIFU and imaging-guided ablation of tumors, which was evaluated both in vitro and in vivo.Results: Both in vitro and in vivo systematical studies validated that the biological targeting synergistic agent can simultaneously achieve tumor-biotargeted multimodal imaging, HIFU synergism and multimodal image monitoring in HIFU therapy. Importantly, the electrostatic adsorption method and the targeting of B. longum to tumor tissues allow the CL-ICG-PFH-NPs to be retained in the tumor tissue, achieve the targeting ability of synergistic agent. Multimodal imaging chose the best treatment time according to the distribution of nanoparticles in the body to guide the efficient and effective treatment of HIFU. CL-ICG-PFH-NPs could serve as a phase change agent and form microbubbles that can facilitate HIFU ablation by mechanical effects, acoustic streaming and shear stress. This lays a foundation for the imaging and treatment of tumors.Conclusion: In this work, a biological targeting synergistic agent was successfully constructed with good stability and physicochemical properties. This biological targeting synergistic agent can not only provide information for early diagnosis of tumors but also realize multimodal imaging monitoring during HIFU ablation simultaneously with HIFU treatment, which improves the shortcomings of HIFU treatment and has broad application prospects.Keywords: high-intensity focused ultrasound, nanoparticles, photoacoustic imaging, fluorescence imaging, ultrasound imaging, image-guided therapy